Electricity Supply and Management Challenges in Nigeria: A Study of BEDC - IKENGA, Francis A.; OGIDIGBEN,, E. Allison (Jurnal Transparansi Publik (JTP), 2023)
Electricity supply situation in Nigeria can be best described as a total failure. It is highly insufficient and unavailable in some places regardless of the huge demand for its service. Successive administrations have voted huge amount of money to the power sector; yet, power outage is a commonplace in the country. It is on this background that this study examined the leading cause of the challenges in the Nigerian power sector over the years. To achieve this specific objective, the study finds it necessary to adopt historical research design and relied extensively on secondary sources of data through the survey of textbooks, journal publications, dailies and internet sources to gather relevant materials for the study. The study finds out that in spite of the policy reforms and funds allocated to the power sector by successive administrations in Nigeria, the sector is yet to be applauded for increase in power supply. In the face of the unending challenge of power outage in Nigeria, this study suggests among others that: the government should allocate sufficient funds to the sector and ensure that funds are utilised for the purposes of which they are allocated, experts in the area should be allowed to manage the sector, technical equipments should be adequately managed and replaced when necessary.